Developing the patients' loyalty model for medical tourism industry: The case of Malaysia - Zainudin, Awang; Asyraf, Aftanorhan; Sharifah Fazella, . (2017)
Medical tourism is nothing new for certain develop and developing countries. This industry is a good money generator to help economic growth and balance of payment of a country. This paper will identify several issues faced by Malaysia in its quest to remain competitive in this industry. The study is aimed to determine which factor is the most importance in providing a high contribution towards medical tourism. This research work assessed four dimensions under human capital construct, and also four dimensions under the physical infrastructure construct. The study also included one mediator construct linking the relationship between each exogenous construct and the intended endogenous construct namely the behavioural loyalty. The study employed stratified sampling method to obtain random sample from foreign tourists seeking treatments in three cities namely Kuala Lumpur, Malacca and Penang. The study utilises partial least square path modelling (PLS-PM). Finally, the result revealed that human capital, high technology, physical infrastructure, and patient satisfaction have positive impact on patient loyalty. Furthermore, the human capital construct was seemed the most importance factor in contributing to the success of medical tourism.